Análise do músculo quadríceps femoral antes e após artroplastia total do joelho por meio do estudo imunohistoquímico - Kawatake, Ednei Haruo [UNIFESP] (2022)
Background: The number of total knee arthroplasties (TKA) has increased steadily with the aging of the population. This surgical procedure is recognized for its success in pain relief and restoration of knee function. However, decreased quadriceps femoris (QF) muscle strength after TKA is frequently observed but with unknown etiology. Evidence suggests that the location of the operative incision (i.e., surgical access) can influence QF muscle structure and function. The present study aimed to assess the fiber type composition, structure and assembly of the QF's vastus medialis (VM) and vastus lateralis (VL) muscles before and after TKA. Methods: Muscle biopsies (VM and VL muscles) were collected from patients previously submitted to TKA via the medial parapatellar route and undergoing TKA revision (main group, n=9) and patients with osteoarthrosis (OA) who will undergo TKA (control group: n=18). The biopsied muscle tissue was prepared, stored, and then sectioned in a cryostat at -25ºC. The tissue sections were evaluated using routine staining techniques in pathological anatomy and histochemistry. Results: The normal mosaic pattern of the medial and lateral knee muscles was observed in the main and control groups, with no evidence of peripheral nerve damage. Notably, 88.9% of the patients exhibited mild to severe VL atrophy, while only 11.1% of patients in the control group presented this feature (p<0.001). Conclusions: The medial parapatellar incision for TKA surgical access does not generate definitive morphological changes in the VM and VL muscle fibers but may contribute to VL atrophy.